MANAJEMEN RETRIBUSI PELAYANAN PASAR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH PEMERINTAH KOTA PEKANBARU - Ilya; Gusnardi; Kartikowati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Regional Original Income (PAD) in Pekanbaru City is still not good. This is because the target set by the Pekanbaru City government has not been achieved for the last 5 (five) years. Regional levies are local levies as payment for certain services and permits specifically provided and/or granted by local governments for the benefit of individuals or organizations. One example is the Retribution for Garbage/Cleaning Services, Parking Services, and Market Services. Market services are traditional/simple market facilities in the form of kiosks and stalls managed by the government for traders. Pekanbaru City has 6 UPTD Markets, none of which has reached the target of realization for the last 3 years. Only about 92.47% of the most realized realizations were paid off from the target. There are still many obstacles in the management of market retribution activities. So that the existence of these problems certainly has an influence on increasing market levies in Pekanbaru City. If POAC management is applied in the perspective of HR management, the management of market service retribution in the city of Pekanbaru can increase or reach the target every year, not only from HR management from the market sector but also HR management from traders in order to fulfill their obligations as traders who enjoy facilities from the government. If the management of human resources from the market sector and traders is paid for, it will automatically increase the income for local revenue, especially in the city of Pekanbaru.